(untitled) (Scientific journal of the Fergana State University, 2026)
Enlightenment is not only the dissemination of knowledge and culture but also a process aimed at transforming the consciousness, reasoning, and behavior of individuals. This process seeks the intellectual development of society through educational systems and cultural activities. Furthermore, enlightenment refers to the educational and intellectual frameworks established within a state or society. These frameworks evolve according to changing historical conditions and are closely linked to economic, political, and cultural factors. This article discusses the central ideas, emergence, and development of the concept of enlightenment, particularly focusing on the movement of enlightened thinkers. From the perspective of Immanuel Kan’s philosophy, enlightenment is expressed not only in external freedom but also in internal freedom. Internal freedom, in this context, refers to the individual’s right to use their reason autonomously and to express their thoughts freely. Consequently, Kant’s conception of enlightenment emphasizes, above all, the right of the individual to self-awareness and the independent application of their intellectual capacities. Western philosophers characterize “immaturity” as a condition in which an individual avoids or fears the independent use of their own reason. This condition manifests when a person relies solely on the guidance, advice, or support of others. According to these thinkers, this state arises from a lack of courage to fully engage with one’s internal strength and intellect. Such immaturity is often perpetuated through the external control and authoritative teachings imposed by social, governmental, or religious institutions. Therefore, enlightenment encompasses not only external social transformations but also an intrinsic need for self-awareness and the autonomous